Racing against Time: Huge Multiple Mass on the Neck - Kurian, Vinay Babu; Shetty, Anil; S., Raveendra U. (Journal of Health and Allied Sciences NU, 2016)
Defining, describing and identifying 'difficult' airways are difficult tasks. The majority of difficult patients that anesthesiologists encounter look 'more-or-less' normal. Anesthesiologists must be prepared to adapt their technique if difficulty occurs. There can be no doubt that the advent of the laryngeal mask airway (LMA) has decreased the frequency of difficulty with the airway. Flexible fiberoptic in tubation is a tremendously useful technique, which every anesthesiologist should attempt to master. The advantage of vision, the pre-eminent sense, needs no explanation.
Keywords: Difficult airway; Fiberoptic intubation; Intubating LMA; Fastrach; Capnography